KAJIAN STRATEGI DAN PROGRAM PERBAIKAN OPERASIONALISASI DARI MILK DISTRICT MODEL NESTLÉ DI JAWA TIMUR - Bambang Ali Nugroho (Buletin Peternakan, 2011)
The objective of this study was to explore the improvement of Nestle milk district model in East Java. Secondary data on dairy development in East Java was used to analyse internal and external factors. SWOT analysis method was used to evaluate existing condition of dairy development in East Java and to build a recomended strategy to improve milk district model. In simplest terms, setting up a milk district involved: a) negotiating agreements with farmers for twice-daily collection of their milk, b) installing chilling centers in the larger community and collection points in the villages or adapting existing collection infrastructure, c) arranging transportation from collection centers to the district’s factory, and d) implementing a program to improve milk quality. In reality building a milk district model is not core business or core competence of Nestle but its something absolutely necessary to be introduced. After this program have been introduced, the smallscale dairy farmers were capable to organise themselves to produce freshmilk. Nestle have introduced various insentive systems to support smallscale dairy farmers capacity to guarantee that they have self responsability in dairy farming activities have positive impacts on productivity, quality product and product safety, that all that aspects will give benefit to Nestle.(Key words: Milk district model, Dairy farmer, Dairy cooperative, Milk processing industry, Strategy, Program)